Investigation of lipophilic substances of the leaves and flowers of spindle tree (Euonymus Europaea L.) - O. R. Vrubel; A. R. Zin; V. O. Antonyuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Spindle Tree (Euonymus europaea L.) has long been used in folk medicine for the treatment of dermatomycoces and as an antiparasitic and anthelmintic agent. However, with what substances it is associate this activity, it is not known for certain. In a previous work, a was developed extracting scheme from the bark of Spindle Tree (Euonymus europaea L.) to obtain water-soluble and lipophilic substances and the composition of the lipophilic fraction was studied using the GC-MS method. The purpose of this work was to obtain lipophilic substances from the flowers and leaves of Spindle Tree and to compare their chemical composition with the composition of substances obtained from the bark of the plant. Flowers and leaves were dried in a drying oven at a temperature of 52 °C, after which a fraction of lipophilic substances was obtained by extraction with petroleum ether. This fraction was analyzed using gas chromatography-mass spectrometry (GC-MS). For this, a chromatographic column was used, which was washed with methanol (model NR-5ms, length 30 m, diameter 0.25 mm, filler: 95% dimethylpolysiloxane + 5% diphenylpolysiloxane; carrier gas ‒ helium with a constant flow of 1.5 ml/min) and 6C / MS Agilent Technologies 6890 N / 5975 B mass spectrometer (USA). The etxtraction by petroleum ether was obtained fraction of lipophilic substances in the amount of 0.83% of the taken weight of dried flowers and 0.62% by weight of dried leaves. In total, 28 compounds were detected in flowers, and 19 in leaves. It was established that flowers and leaves of Spindle Tree, like bark, are characterized by a high content of paraffinic carbohydrates (from C20H42 to C31H64). Their content is higher in flowers (more than 50% of the composition of the fraction), and in leaves and bark ≈ 35%. Steroid and terpene compounds in the lipophilic fractions of the leaves and bark of the plant are respectively 28.26% and 24.32%. Among them quantitatively dominated by freedeen. A rather high content of squalene (2.06%) was found in the leaves of the plant. Among other compounds, a significant proportion of fatty acids and their esters, of which 24.59% by weight of the lipophilic fraction of flowers and 14.74% by weight of the lipophilic fraction of leaves. An analysis of the results indicates a greater promise for the use in medicine of lipophilic substances of the bark and leaves of Spindle Tree than of flowers.